Analisis tentang Kebijakan Pemerintah Kabupaten Jember dalam Memberikan Perlindungan terhadap Lahan Pertanian Pangan Berkelanjutan - Arum Sabil, Muhammad; ., Supianto; Tri Budiman, Nanang; Laily Mufid, Firda (WELFARE STATE Jurnal Hukum, 2024)
The recent conversion of agricultural land for food has caused the area of food agricultural land to shrink and is feared to have an impact on decreasing food production. Land use for housing is growing rapidly, along with developments in population and the economic level of society. Rice fields in Jember Regency continue to experience shrinkage. Therefore, there is a need for policies from local governments to provide sustainable food agricultural land protection. This research aims to analyze the protection arrangements for food agricultural land from being converted to non-agricultural use and analyze the policies of the Jember Regency Government in regulating the protection of sustainable food agricultural land. The research method used for this writing uses a normative juridical research type (legal research) with a statutory (statute approach) and conceptual (conceptual approach). The results obtained in this research are that land conversion does not occur naturally, but is caused by several factors that encourage land conversion to occur. Jember Regency Government policy in an effort to protect sustainable food agricultural land includes, among other things, issuing Jember Regency Regional Regulation Number 1 of 2015 concerning RTRW for 2015-2035. In this Regional Regulation, a policy regarding the protection of sustainable food agricultural land has been established.